UMP student wins Innovate Malaysia Excellent Award Special Award - Mimi Rabita, Abdul Wahit (2021)
KUANTAN, 9 August 2021 - A student from the College of Engineering (KKEJ), Universiti Malaysia Pahang (UMP), Lim Wei Jie, was named the winner of the Innovate Malaysia Excellent Award 2021 Special Award and won first place for Intel Technology Track in the online Innovate Malaysia Design Competition recently.